2007
DOI: 10.1016/j.annepidem.2006.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Breast Cancer Risk Among Women in the Southwestern United States

Abstract: Physical activity may influence breast cancer risk through multiple mechanisms and at different periods in life. In this study we evaluate breast cancer risk associated with total and vigorous physical activity at ages 15, 30, and 50 years and the referent year prior to diagnosis/selection. Participants were non-Hispanic white (NHW) (1527 cases and 1601 control subjects) and Hispanic/American Indian (HAI) (798 cases and 924 controls) women. Both total and vigorous activity reduced risk of breast cancer in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 34 publications
9
75
2
3
Order By: Relevance
“…HRs for hormone receptor-defined invasive breast cancer according to level of recreational physical activity within the previous 4 years Contrary to most studies, which have not found that the relation between physical activity and breast cancer risk was modified by weight changes before inclusion (9,11,13,21,30), three articles report that the risk decrease associated with baseline physical activity is restricted to postmenopausal women with limited weight gain between youth and baseline (22,31,32). However, a weight gain before baseline may be associated with a decrease in physical activity after baseline (33).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…HRs for hormone receptor-defined invasive breast cancer according to level of recreational physical activity within the previous 4 years Contrary to most studies, which have not found that the relation between physical activity and breast cancer risk was modified by weight changes before inclusion (9,11,13,21,30), three articles report that the risk decrease associated with baseline physical activity is restricted to postmenopausal women with limited weight gain between youth and baseline (22,31,32). However, a weight gain before baseline may be associated with a decrease in physical activity after baseline (33).…”
Section: Discussionmentioning
confidence: 62%
“…However, the leanness of E3N women did not allow to explore the effect in higher categories of BMI or waist circumference. Similarly, most studies did not observe modifications in this relation according to hormone receptor status during postmenopause (6,10,13,(22)(23)(24)(25)(26). The risk reduction was limited to ER À (27) and PR þ (28) subtypes in two prospective studies and apparent only for postmenopausal ER þ /PR À (29) and ER þ /PR þ (25) cancers in two other studies (no tests for homogeneity).…”
Section: Discussionmentioning
confidence: 99%
“…The Four-Corners Breast and Endometrial Cancer Study (Arizona, New Mexico, Colorado, and Utah-all in the Southwest IHS region), for example, was designed to examine genetic admixture in relation to gene markers and environmental factors among American Indian, Hispanic, and NHW women. 30,31 Studies of breast cancer risk factors and genetic markers also are needed among AI/AN populations in other regions. In Alaska, for example, widespread exposure to organochlorines has been documented, buts its association with breast cancer is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha demostrado que elevados niveles de actividad física están asociados a niveles inferiores de marcadores de inflamación, el estrógeno ha mostrado ser proinflamatorio, y otros estrógenos como el 17 betaestradiol poseen una función inhibidora de la expresión del gen inflamatorio, que es regulado por el factor nuclear kB (McTiernan et al, 2003;McTiernan, Ulrich, Slate y Potter, 1998;Slattery et al, 2007).…”
Section: Alterando La Respuesta Inflamatoriaunclassified